In silico study of fucoxanthin as a tumor cytotoxic agent - Hedi I Januar; Ariyanti S Dewi; Endar Marraskuranto; Thamrin Wikanta (Wolters Kluwer Medknow Publications, 2012)
Background: Fucoxanthin is a potential tumor cytotoxic compound. However, mechanisms underlying the activities are unclear. Aim: This in silico study aimed to predict the main mechanism of fucoxanthin; whether with its binding to p53 gene, CDK2, or tubulin. Materials and Methods: In silico was studied by using Autodock-Vina's algorithms. The mechanisms being analyzed by comparison of fucoxanthin and native ligands binding energies in p53 gene (1RV1), CDK2 (1AQ1), and three binding sites of tubulin (1JFF-paclitaxel, 1SA0-colchicine, and 1Z2B-vinblastine site). Results: Autodock-Vina's algorithms were valid, as re-docking the native ligands to their receptors showed a RSMD value less than 2 A with binding energies of -11.5 (1RV1), -14.4 (1AQ1), -15.4 (1JFF), -9.2 (1SA0), and -9.7 (1Z2B) kcal/mol. Docking of fucoxanthin to subjected receptors were -6.2 (1RV1), -9.3 (1AQ1), -8.1 (1JFF), -9.2 (1SA0), and -7.2 (1Z2B) kcal/mol. Virtual analysis of fucoxanthin and tubulin binding structure showed the carboxyl moiety in fucoxanthin make a hydrogen bound with 355Val (2.61 A) and 354Ala (2.79 A) at tubulin. Conclusion: The results showed that binding energy of fucoxanthin could only reach the same level as with colchicine ligand in tubulin. Therefore, it may predict that the most probable fucoxanthin main mechanism is to bind tubulin, which causes microtubules depolimerization and cell cycle arrest.